From Centralized Authority to Shared Vision: Collective-Transformational Leadership in Pesantren - Sutrisno Sutrisno; Ethem Gürhan; Muhtar Hazawawi (Al-Insyiroh: Jurnal Studi Keislaman, 2026)
The sustainability of faith-based educational organizations often relies heavily on the singular charisma of their founders, making them highly vulnerable to institutional collapse upon the founder's demise ("founder's syndrome"). This study explores the actualization of collective-transformational leadership and its impact on shaping organizational culture within traditional Pesantren. Employing a qualitative multiple-case study design, research was conducted across three distinct institutional models: the Federation, Modern, and pure Traditional models. Data were collected over six months through in-depth interviews with nearly 30 participants—including central clerics, senior teachers, and students—complemented by participant observation and document analysis. The cross-case thematic analysis reveals a strategic structural shift from solitary, founder-centric authority to formalized, shared leadership councils. This transition successfully institutionalizes the clerics' charisma rather than diluting it. Furthermore, through informal communication strategies and spiritual synergy, this collective leadership mitigates internal conflicts and inspires the organizational community. Consequently, this shared authority shapes resilient and agile organizational cultures tailored to specific institutional visions, ranging from socio-environmental activism and global modern integration to the robust preservation of classical scholasticism. Theoretically, this study expands transformational leadership discourse by demonstrating that charismatic influence can operate synergistically as a collective phenomenon. Practically, it offers a sustainable governance blueprint for global faith-based organizations navigating the tension between preserving traditional religious identity and adapting to modern educational complexities